2022
DOI: 10.1038/s42003-022-03605-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose sodium-glucose cotransporter 2 inhibitor ameliorates ischemic brain injury in mice through pericyte protection without glucose-lowering effects

Abstract: Antidiabetic sodium-glucose cotransporter 2 (SGLT2) inhibitors have attracted attention for their cardiorenal-protective properties beyond their glucose-lowering effect. However, their benefits in ischemic stroke remain controversial. Here we show the effects of luseogliflozin, a selective SGLT2 inhibitor, in acute ischemic stroke, using a permanent middle cerebral artery occlusion (pMCAO) model in non-diabetic mice. Pretreatment with low-dose luseogliflozin, which does not affect blood glucose levels, signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Finally, our study demonstrates the potential of a post-stroke intervention with SGLT2i to improve recovery in T2D. Of interest in this respect was a recent study of Takashima and colleagues, demonstrating that a low-dose pre-stroke treatment with Luseogli ozin in non-diabetic mice, not affecting urinary glucose levels, could signi cantly decrease infarct size and improve neurological recovery (29).…”
Section: Discussionmentioning
confidence: 55%
“…Finally, our study demonstrates the potential of a post-stroke intervention with SGLT2i to improve recovery in T2D. Of interest in this respect was a recent study of Takashima and colleagues, demonstrating that a low-dose pre-stroke treatment with Luseogli ozin in non-diabetic mice, not affecting urinary glucose levels, could signi cantly decrease infarct size and improve neurological recovery (29).…”
Section: Discussionmentioning
confidence: 55%
“…The effect of SGLT2i on an ischemic stroke is controversial. However, a recent study has shown that inhibition of SGLT2 prior to stroke increases ischemic tolerance in pericytes and improves ischemic brain injury . Atherosclerosis is a chronic inflammatory vascular disease in which plaques form in the intima of the vessels involving various cells, lipids, and debris .…”
Section: Discussionmentioning
confidence: 99%
“…SLC5A2, namely the SGLT2 gene, was reported to be the drug target for SGLT2 inhibitors, hence the spatial distribution of SLC5A2 would provide insights into the target tissues of SGLT2 inhibitors [ 34 ]. Takashima and colleagues have demonstrated that low-dose luseogliflozin ameliorates ischemic brain injury in mice without glucose-lowering effects [ 35 ]. Similarly, Joki et al have shown that tofogliflozin modulates pulmonary vascular remodelling in mice with left heart disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%